Enhancing Students’ Writing Ability by Implementing Team Stand-N-Share Strategy - Sayid Ma’rifatulloh; Mohammad Adnan Latief; Yazid Basthomi (Jurnal Pendidikan Humaniora, 2015)
Abstract: This Collaborative Classroom Action Research was aimed at improving the students’ writing ability in recount text at Junior High School (SMP) TTN Paculgowang Jombang, East Java, Indonesia in Academic Year of 2014/2015. The subjects of this study were students of class VIIIA. The instruments in collecting the data were observation checklists, questionnaire, field notes and the students’ writing test. The results of the study show that there were improvement of the students’ participation and  im-provement of the students’ writing ability. From the data collected through students’ questionnaire, the researcher found out that most of the students had positive response toward the implementation of Team Stand-N-Share strategy.Key Words: team stand-n-share, writing ability, recount textAbstrak: Penelitian tindakan kelas kolaborasi ini bertujuan untuk meningkatkan kemampuan menulis siswa dalam teks rekon di SMP TTN Paculgowang Jombang, Jawa Timur, Indonesia tahun akademik 2014/2015. Subjek penelitian adalah siswa kelas VIIIA. Instrumen dalam pengumpulan data adalah daftar periksa observasi, angket, catatan lapangan dan ujian menulis siswa. Hasil penelitian menunjuk-kan bahwa ada peningkatan partisipasi siswa dan peningkatan kemampuan menulis. Dari data yang dikumpulkan melalui kuesioner siswa, ditemukan bahwa sebagian besar siswa memiliki respon positif terhadap pelaksanaan strategi Team Stand-N-Share.Kata kunci: team stand-n-share, kemampuan menulis, teks rekon